Biological Features and The Mortality Life Table of Aleyrodes lonicerae Walker (Hemiptera: Aleyrodidae) on Viola tricolor L. - Bağdel Çelik; Tülin Özsisli (Turkish Journal of Agriculture: Food Science and Technology)
Biology of the lonicera whitefly, Aleyrodes lonicerae Walker (Aleyrodidae: Hemiptera) were studied on violet, Viola tricolor L. (Violaceae) plants. Whitefly adults were collected from Mercurialis annua L. (Euphorbiaceae) plants in Adana. The development duration of egg, first, second, third, fourth larval (pupa) stages of A. lonicerae on V. tricolor were 9.17, 6.33, 5.83, 4.00, 5.17 and 30.50 days for the females and 10.27, 5.91, 5.55, 4.82, 4.55 and 31.10 days for the males, respectively. The total development duration from egg to adult of female and males of A. lonicerae were 30.50 and 31.10 days. The mortality rate (%) of egg, 1., 2., 3. and 4. larva (pupae) stages on violet leaves were 22.45, 18.37, 12.25, 4.08 and 8.16, respectively. According to life table depending on pre-adult stages on violet plants, the biggest k value determined was for the first larvae stage (k=0.1174). At the same time, the k-values determined indicated the stage with the highest mortality rates. In the studies conducted for host plant preference, the average numbers of eggs deposited by the females of A. lonicerae were significantly different between rose (2.67/two leaves) and violet (15.83/two leaves) in the same experimental area. The study was conducted in a climate-controlled room in at 20±2°C, 40%±5 relative humidity.